STUDY ON THE DISPOSAL OF WASTE FROM THE HYDROGEN GENERATION BY ALUMINUM OXIDATION IN ALKALINE SOLUTION - Jacob-Furlan, B.; Souza, G. B. M.; Filho, L. C.; Hakoyama, D. S.; Reinert, A. P.; Gonçalves, R. S. R.; Sapucaia, M. B. H. R.; Balmant, W.; Taher, D. M.; Silveira, A. M.; Mariano, A. B.; Ordonez, J. C.; et al. (Revista de Engenharia Térmica, 2023)
In face of the current high energy consumption and demand worldwide, a change to a sustainable energy matrix became one of the pillars for global sustainability. The use of renewable energy has been one of the most attractive subjects in recent years. Several public policies in this matter have been suggested and there are ongoing efforts toward their implementation. The United Nations (UN) proposed what is called the 2030 Agenda, which considers 17 Sustainable Development Goals (SDG) to be achieved by the year 2030. In support of the 2030 Agenda, research on the production of fuels from clean and sustainable sources is being conducted by the scientific community around the world. Fossil fuels are finite and also a major source of environmental pollutants, therefore the choice of using renewable sources of energy tends to be an increasingly growing and attractive alternative. Hydrogen is a fuel with a high heating value and is known as the most abundant gaseous element and simplest in chemical structure. The scientific community researching fuel cells has given much attention to the generation and storage of hydrogen. Besides the electrolytic hydrogen production and the reforming of fossil fuels (e.g., natural gas), hydrogen can be generated by metallic means, for example, by oxidation of aluminum in an alkaline solution. The use of recyclable metals, such as aluminum in this study, is an option for sustainable hydrogen generation processes. Nevertheless, like any chemical reaction, part of the products generated are waste, and some are even harmful to the environment, which makes the production of sustainable fuels unfeasible in case of not finding an appropriate technological industrial destination for such waste. The herein study comprises the investigation of the industrial and technological applications of the products of the hydrogen generation reaction from aluminum. Mastering the chemical reaction parameters of that reaction is paramount for the optimal design of a hydrogen generation system. The disposal of the waste is relevant since it makes the energy supply chain complete and sustainable.